Characterization of Endogenous Transglutaminase Enzyme of Yellow Pike Conger’s Liver (Congresox talabon) - SidaurukSanthy Wisuda; Nurhayati, Tati; LaksonoUntung Trimo (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Transglutaminases have been found in various living organism, such as mammals, plants, microorganisms, and marine organisms including fishes. Transglutaminases have many various functions such as food or non-food application and in pharmaceticals industries. This research was aimed to characterize transglutaminase that obtained from fisheries byproducts such as catadromous fish the yellow pike conger’s liver.. The yield of yellow pike conger’s liver was 0.88±0.11%. Crude transglutaminase from liver of yellow pike conger had specific activity of 1.375 U/mg with optimum pH at 7.5 and optimum temperature at 50°C. The activity of transglutaminase were increased on Mg2+ ion dependent. Crude transglutaminase had molecular weight of 27.48; 37.00; 69.51; 78.89; 88.18; 108.45; 134.10; and 172.12 kDa.